2009
DOI: 10.1017/s136898000900528x
|View full text |Cite
|
Sign up to set email alerts
|

Unhealthy dietary patterns are associated with weight gain during pregnancy among Finnish women

Abstract: Objective: To study whether the dietary patterns of Finnish pregnant women are associated with their weight gain rate during pregnancy. Design: A validated 181-item FFQ was applied retrospectively to assess the diet during the eighth month of pregnancy, and maternal height and maternal weight at first and last antenatal visits were recalled. Information on sociodemographic characteristics, parity and smoking of the pregnant women was obtained by a structured questionnaire and from the Finnish Birth Registry. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
90
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 35 publications
12
90
1
2
Order By: Relevance
“…It has been previously shown that a ‘fast food’ dietary pattern was associated with weight gain rate during pregnancy in a dose-dependent manner in a study conducted in Finland [40]. The result of that study is indirectly supportive of our findings.…”
Section: Discussionsupporting
confidence: 91%
“…It has been previously shown that a ‘fast food’ dietary pattern was associated with weight gain rate during pregnancy in a dose-dependent manner in a study conducted in Finland [40]. The result of that study is indirectly supportive of our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Few studies have explored dietary patterns in relation to GWG. Uusitalo et al reported a dose-response association of a 'fast-food pattern' with rate of GWG, whereas an inversely associated 'healthy pattern' was not statistically significant (30) . Stuebe et al investigated associations of several dietary and nutritional aspects with risk for excessive GWG in 1388 pregnant women and found total energy intake, dairy and fried foods to be directly associated with risk of excessive GWG, whereas a vegetarian diet in the first trimester was inversely associated with excessive GWG (31) .…”
Section: Discussionmentioning
confidence: 97%
“…In a prospective study, pre-pregnancy body mass index was a stronger predictor of GDM than diet quality during pregnancy [24]. A high weight gain rate during pregnancy may also be relevant to the pathophysiology of GDM [31,32]; the ‘fast food’ dietary pattern (characterized by higher consumption of sweets, soft drinks, hamburgers, pizza and other fast foods), in a dose-dependent manner, has also been associated with higher weight gain during pregnancy [33]. Moreover, dietary factors such as refined and high-glycemic-index carbohydrates are other threatening factors that may contribute to impaired insulin secretion and pancreatic β-cell function, and induced insulin resistance before pregnancy [34], and lead to GDM during pregnancy [12,35].…”
Section: Discussionmentioning
confidence: 99%